Survival analysis of a 16-year cohort of follicular lymphoma patients receiving systemic treatment in Brazil - Pamela Santos Azevedo; Isabella Zuppo Laper; Deborah Marta do Santos Oliveira; Adriano de Paula Sabino; Marina Morgado Garcia; Isabela Cristina Menezes de Freitas; Isabela Cristina Menezes de Freitas; Wallace Mateus Prata; Wallace Mateus Prata; Mariângela Leal Cherchiglia; Juliana Álvares-Teodoro; Juliana Álvares-Teodoro; et al. (Frontiers in Pharmacology)
IntroductionFollicular lymphoma (FL) is a common type of non-Hodgkin lymphoma that is incurable but often follows an indolent course. While survival is improving thanks to advances in diagnosis, supportive care, and new therapies, understanding outcomes and their impact on overall survival is still limited. There are few studies on FL in Brazil, so this study aims to evaluate the patient’s profile, morbidity and mortality treated by the Brazilian national health service (SUS) and evaluate risk factors associated with treatment failure.MethodsThis is a nationwide 16 years cohort with patients that underwent chemotherapy in the SUS (2000–2015). The Kaplan-Meier method was used to estimate survival until treatment failure, and the Cox proportional hazards model was used to evaluate risk factors.ResultsThe cohort included 10,009 patients and survival rates were 73.3%, 45.3%, and 30.7% for the first, fifth and 10th year respectively. The median overall survival was approximately 4.1 years. The most used regimen was CHOP (13%), followed by CVP (9.7%) and R-CHOP (3.3%). Four hundred and ninety-eight patients (4.9%) used rituximab-containing regimens. Univariate analysis indicated worse survival rates for male patients, those over 65 years of age, clinical stage III or IV and those using non-rituximab-containing regimens. The health technology performance assessment related to oncology schemes for FL suggests that rituximab-based regimens has shown best survival probability (0.52 CI 0.39–0.69) in 78 months of follow up with a HR 1.5 times better than other schemes (HR 0.67; CI 0.55–0.81).DiscussionIn light of the substantial advancements achieved by the SUS, there is a need for CONITEC to expedite decision-making processes in order to enhance patients access to new oncology drugs. This should be done while upholding health technology assessment standards. Timely integration and sufficient funding for oncology services have the potential to save lives, especially when compared to the treatments available within SUS at that time.